2021
DOI: 10.14283/jpad.2021.56
|View full text |Cite
|
Sign up to set email alerts
|

Donanemab (LY3002813) Phase 1b Study in Alzheimer’s Disease: Rapid and Sustained Reduction of Brain Amyloid Measured by Florbetapir F18 Imaging

Abstract: Background: Donanemab (LY3002813) is an IgG1 antibody directed at an N‑terminal pyroglutamate of amyloid beta epitope that is present only in brain amyloid plaques. Objectives: To assess effects of donanemab on brain amyloid plaque load after single and multiple intravenous doses, as well as pharmacokinetics, safety/tolerability, and immunogenicity. Design: Phase 1b, investigator- and patient-blind, randomized, placebo-controlled study. Setting: Patients recruited at clinical research sites in the United Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(74 citation statements)
references
References 25 publications
2
71
0
1
Order By: Relevance
“…Donanemab is an immunoglobulin G1 antibody specific for an epitope that is only present in mature brain amyloid plaques. 1 , 2 Donanemab treatment resulted in rapid and deep clearance of amyloid plaques as shown by [ 18 F] florbetapir positron emission tomography (PET) in phase 1 studies. 1 , 3 …”
Section: Introductionmentioning
confidence: 99%
“…Donanemab is an immunoglobulin G1 antibody specific for an epitope that is only present in mature brain amyloid plaques. 1 , 2 Donanemab treatment resulted in rapid and deep clearance of amyloid plaques as shown by [ 18 F] florbetapir positron emission tomography (PET) in phase 1 studies. 1 , 3 …”
Section: Introductionmentioning
confidence: 99%
“…Given the potential clinical significance and market effects of AD therapeutics, there have been many attempts to target Aβ using various approaches focusing on different stages of the amyloid cascade ( Table 1 ) [ 185 - 228 ]. For example, inhibitors of Aβ-related secretases aim to decrease the production of Aβ itself as a preventative measure, while anti-Aβ immunotherapies induce partial or complete clearance of Aβ at the end of the amyloid cascade.…”
Section: Aβ-directed Therapeutics In Clinical Trials and Implicationsmentioning
confidence: 99%
“…Donanemab binds to N-terminal pyroglutamate Aβ (AβpE3-42) which exists exclusively on amyloid plaques. A recent phase 1b florbetapir PET imaging study involving 61 AD patients demonstrated strong plaque-clearing ability ( Lowe et al, 2021 ).…”
Section: The Current Status Of Amyloid-targeting Experimental Therape...mentioning
confidence: 99%